2017
DOI: 10.1080/14606925.2017.1352916
|View full text |Cite
|
Sign up to set email alerts
|

Who’s in charge? End-users challenge graphic designers’ intuition through visual verbal co-design

Abstract: This paper aims to understand how co-design influences the design process, by presenting a case study where graphic designers and end-users codesigned asthma information. Three co-design activities are presented, as part of a larger project, revealing insights for the next generation of graphic designers. The co-design activities built a trusting, enjoyable environment, while posing the question are designers still in charge of the process? A visual verbal game dissolved participant status barriers, a persona … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This situation might not change until graphic designers overcome the 'fear that sharing will "give away" some perceived competitive edge' (Frascara, 2004, p. 60). In response, Taffe (2017) found that co-designing with end users can yield more creative solutions if graphic designers relinquish creative control while still relying firmly on their intuition during the creative process.…”
Section: Intuition In Graphic Designmentioning
confidence: 99%
“…This situation might not change until graphic designers overcome the 'fear that sharing will "give away" some perceived competitive edge' (Frascara, 2004, p. 60). In response, Taffe (2017) found that co-designing with end users can yield more creative solutions if graphic designers relinquish creative control while still relying firmly on their intuition during the creative process.…”
Section: Intuition In Graphic Designmentioning
confidence: 99%
“…It is easy to use and its limitations in practical usage, for the design assignment tasks that it was set, appear to be more focussed on its data set and training. However, such limitations may also be reflective of the difficulty of aligning the intangible nature of some of the more conceptual and creative aspects of many design practices (Heller 2019), for example, intuition (Taffe 2017), as well as in design’s inherent interdisciplinarity (Harland 2015), with the more empirical principles of computer science based AI. Such limitations may also be partially attributable to the relative nascency of academic rigour in some of those design disciplines, such as graphic design (Corazzo et al 2019), which in turn may cast limitations on the data that ChatGPT is able to draw on.…”
Section: Methodsmentioning
confidence: 99%
“…Surveys, questionnaires, focus groups and interviews are all useful to gain feedback on prototypes, as well as on the specific design elements. Mixing and matching cards with different design elements and their potential meanings could elicit feedback on risk interpretations [129]. An expert review of the prototypes could reveal hitherto hidden aspects [130].…”
Section: Designmentioning
confidence: 99%